2022
DOI: 10.48550/arxiv.2207.08560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latency-Aware Collaborative Perception

Abstract: Collaborative perception has recently shown great potential to improve perception capabilities over single-agent perception. Existing collaborative perception methods usually consider an ideal communication environment. However, in practice, the communication system inevitably suffers from latency issues, causing potential performance degradation and high risks in safety-critical applications, such as autonomous driving. To mitigate the effect caused by the inevitable latency, from a machine learning perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In the past decade, the attention mechanism has played an increasingly important role in computer vision [13,57,69,70], which also inspires collaborative perception research. Since feature selection and relationship exploring are vital issues in intermediate collaborative perception, some works [21,23,29,71,72,73,74] leverage attention mechanisms to exploit more dynamic and robust collaborative perception strategies. Due to flexibility, attention-based design becomes the dominant strategy in intermediate collaboration.…”
Section: A Improve Collaboration Efficiency and Performancementioning
confidence: 99%
See 3 more Smart Citations
“…In the past decade, the attention mechanism has played an increasingly important role in computer vision [13,57,69,70], which also inspires collaborative perception research. Since feature selection and relationship exploring are vital issues in intermediate collaborative perception, some works [21,23,29,71,72,73,74] leverage attention mechanisms to exploit more dynamic and robust collaborative perception strategies. Due to flexibility, attention-based design becomes the dominant strategy in intermediate collaboration.…”
Section: A Improve Collaboration Efficiency and Performancementioning
confidence: 99%
“…Therefore, it is of great practical significance to ensure robustness and safety for collaboration perception. In this subsection, we focus on advanced research on these issues and summarize collaborative modules designed to address these issues [21,24,31,53,74,85,86].…”
Section: B Ensure Collaboration Robustness and Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Sooner or later, these autonomous systems will be deployed on roads at scale, opening up opportunities for cooperation between them. Previous works in [4], [5], [6], [7], [8], [9], [10], [11], [12] have demonstrated that by leveraging the Vehicle-to-Everything (V2X) communication technology, AVs and infrastructure can perform cooperative perception by using the shared sensing information and thus significantly enhance the perception performance. Despite the remarkable improvement, these works evaluate the proposed systems on the dataset with natural scenarios that do not contain sufficient safety-critical scenes.…”
Section: Introductionmentioning
confidence: 99%